Effect of Biobriquette Composition Made from Peanut Shells and Wood Powder on Calorific Value and Burning Rate - Halimatus Sakdiah, Nur; Pangga, Dwi; Ahzan, Sukainil (Prodi Fisika FKIP Unram, 2023)
This research aims to determine the effect of the composition of biobriquettes made from peanut shells and wood dust on the calorific value and combustion rate. This research is experimental research carried out in three stages, namely material preparation, making biobriquettes, and testing biobriquettes. The manufacturing process uses a simple briquette press. For the composition, Peanut Shell Charcoal (AKKT) + Wood Powder Charcoal (ASK) with an adhesive percentage of 10%, namely 0%+90%; 15%+75%; 30%+60%; 45%+45%; 60%+30%; 75%+15%; 90%+0%. The research results show that the calorific value ranges from 7387-1806 calories and the combustion rate ranges from 3.81-1.51 grams/minute. Based on the research results, it was found that the greater the AKKT composition, the higher the calorific value, while the resulting combustion rate was lower. So in the future, this research can be developed to make it better and better for making briquettes. Keywords: biobriquettes, peanut shells, wood dust.